2023
DOI: 10.1002/pul2.12206
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SELPLG/P‐selectin glycoprotein ligand 1 in preclinical ARDS: Genetic and epigenetic regulation of the SELPLG promoter

Abstract: We previously identified a missense single nucleotide polymorphism rs2228315 (G>A, Met62Ile) in the selectin-P-ligand gene (SELPLG), encoding P-selectin glycoprotein ligand 1 (PSGL-1), to be associated with increased susceptibility to acute respiratory distress syndrome (ARDS). These earlier studies demonstrated that SELPLG lung tissue expression was increased in mice exposed to lipopolysaccharide (LPS)-and ventilator-induced lung injury (VILI) suggesting that inflammatory and epigenetic factors regulate SELPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…The hypoxemia is one of the main intermediate mechanisms of OSA. In this regard, a recent study reported that PSGL-1 expression increased susceptibility in patients with acute respiratory distress syndrome, demonstrating the PSGL-1 promoter activity was strongly regulated by HIF-1α and HIF-2α ( 39 ). Remarkably, hypoxia develops in most solid tumors because of the rapid growth of the tumor that outstrips the oxygen supply, and is one of the main hallmarks of tumor microenvironment ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypoxemia is one of the main intermediate mechanisms of OSA. In this regard, a recent study reported that PSGL-1 expression increased susceptibility in patients with acute respiratory distress syndrome, demonstrating the PSGL-1 promoter activity was strongly regulated by HIF-1α and HIF-2α ( 39 ). Remarkably, hypoxia develops in most solid tumors because of the rapid growth of the tumor that outstrips the oxygen supply, and is one of the main hallmarks of tumor microenvironment ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, additional studies are needed to understand the implications of PSGL-1 axis in the context of OSA-related tumor initiation. On the other side, Sun et al., suggest that additional inflammatory and epigenetic factors may regulate PSGL-1 expression ( 39 ). Moreover, previous studies indicate an upregulation of PSGL-1 in acute inflammation ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) in Blacks with ARDS identified a coding SNP that influences the activity of the SELPLG-encoded PSGL1 (119). Similar to MYLK, CTTN, and NAMPT, ARDS stimuli increase SELPLG promoter activity via the participation of transcription factors that include HIF-1α/HIF-2α and NRF2 (120).…”
Section: Genetic Influences On Maladaptive Mechanisms That Increase S...mentioning
confidence: 99%
“…PSGL1 is an attractive ARDS target with several approaches to PSGL1 neutralization that have all attenuated lung injury in preclinical ARDS/VILI models. These include the FDA-approved P-selectin-binding humanized mAb, crizanlizumab (119,145), the human anti-PSGL1 mAb (CD162) (119), and TSGL-Ig, a novel recombinant tandem PSGL1 immunoglobulin fusion molecule (120).…”
Section: Lung Endothelium As a Druggable Target In Acute Respiratory ...mentioning
confidence: 99%
“…The therapeutic targeting of SELPLG and its encoded protein, PSGL-1, holds promise in substantially mitigating the severity of in ammatory lung injury, including respiratory distress syndrome (ARDS) and VILI. (Sun et al, 2023) Owing to these ndings, we hypothesized that MAPK1, PIK3CA, and SELPLG may be involved in the onset and progression of COPD via the establishment of NETs that trigger in ammation. Dectin-2 (CLEC6A) has been demonstrated to be correlated to dust mite-induced chronic airway in ammation.…”
Section: Single-cell Sequencing Validation and Single-cell Data Evalu...mentioning
confidence: 99%